Using SMS to monitor adverse events following trivalent influenza vaccination in pregnant women - Regan, Annette; Blyth, C.; Mak, D.; Richmond, P.; Effler, P. (Wiley-Blackwell Publishing Asia, 2014)
Background: Trivalent influenza vaccine (TIV) has been recommended for pregnant women in Australia for more than a decade and funded since 2009, yet vaccination coverage remains low. Misperceptions of the safety of TIV in pregnancy have been identified as a major contributor to low vaccination rates. Ongoing safety monitoring with dissemination of results could help improve antenatal influenza vaccine uptake. Aim: To implement a real-time safety monitoring program for TIV administered to pregnant women. Materials and Methods: Between March and July 2013, a cohort of 3,173 pregnant women who received the 2013 TIV agreed to follow-up regarding possible adverse events following immunisation (AEFI); 3,047 (96%) provided a mobile telephone number and were sent a short message service (SMS) inquiring whether they had experienced an AEFI; attempts were made to contact the remaining 126 (4%) women by voice telephone call. Results: Responses were obtained from 2,885 (90.9%) women, 413 (14.3%) of whom reported a suspected AEFI. Local reactions were the most frequently reported AEFI (4.9%), followed by headache (3.3%), fever (2.7%), fatigue (2.5%), diarrhoea (2.5%) and malaise (1.2%); 39 women (1.4%) sought medical advice and no serious vaccine-related AEFIs were identified. Response rates were higher for SMS compared to telephone (84% vs 63%; P < 0.001). Conclusions: These findings support the safety of TIV in pregnant women. Mobile phone technology proved an efficient method for timely surveillance of adverse events following vaccination. The low level of AEFI observed should be reassuring to antenatal patients and their providers and help promote TIV uptake.